Eclectic Sufism in the Contemporary Arab World - Mark Sedgwick (Tidsskrift for Islamforskning, 2017)
Eclectic Sufism that might be interpreted as a modern form of subjectivity construction has been observed in Morocco and Pakistan. This article reports comparable phenomena elsewhere, using the case of the Arabic translation of Elif Shafak’s novel The Forty Rules of Love. The article argues that, in the wider Arab world as in Morocco and Pakistan, the localization of eclectic Sufism is an instance of the reinterpretation of Islamic traditions to incorporate globally relevant social imaginaries. It questions, however, the association between eclectic Sufism and individualism, and argues that there is also a further form of localization: the application of eclectic Sufism to contemporary political conditions, notably the problem of sectarianism.